2009
DOI: 10.1055/s-2008-1027865
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pantoprazole on Duodeno-Gastro-Esophageal Reflux (DGER)

Abstract: Our data confirm that high-dose pantoprazole therapy effectively exerts acid suppression in GERD patients with combined pathological reflux. However, DGER could only normalised in 50 % of patients. High levels of DGER at diagnosis enhance the risk of persistent DGER under PPI therapy and are associated with a reduced clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…single-dose vs. high-dose pantoprazole) [15,21]. A previous study from our group has shown that only in about 50% of patients with combined pathological reflux (bile and acid) DGER could be normalized by high-dose pantoprazole [19]. Here, we compare the degree of DGER and esophageal acid exposure in a cohort of GERD patients who had a history of incomplete symptom control with PPIs during the past year.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…single-dose vs. high-dose pantoprazole) [15,21]. A previous study from our group has shown that only in about 50% of patients with combined pathological reflux (bile and acid) DGER could be normalized by high-dose pantoprazole [19]. Here, we compare the degree of DGER and esophageal acid exposure in a cohort of GERD patients who had a history of incomplete symptom control with PPIs during the past year.…”
Section: Discussionmentioning
confidence: 99%
“…The catheter was introduced nasally and positioned 5 cm above the lower esophageal sphincter. An episode of acid reflux was defined as a decrease in esophageal pH value below 4 for at least 10 s. A pathological pH measurement was defined for a time with pH values below 4 for longer than 4% of the total 24-hour period [15,19]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies evaluated the treatment of bile reflux (Table 6). The therapies included nine evaluating PPIs, 29‐37 two studies evaluating prokinetics, 38,39 one study evaluating surgery, 29 one evaluating histamine receptor antagonists 40 and one evaluating baclofen 41 . Ten studies utilised Bilitec 2000 as the device to measure bile reflux, three studies used a sodium ion electrode.…”
Section: Resultsmentioning
confidence: 99%
“…All patients were referred to the out‐patients department of the University of Marburg for suspected reflux disease. The pattern of clinical symptoms was evaluated with a questionnaire, specifically designed by our group 33 . The symptoms heartburn, regurgitation, chest pain, dysphagia, nocturnal coughing, wheezing, hoarseness and vomiting were graded according to severity into 1: not existing, 2: mild, 3: moderate and 4: severe.…”
Section: Methodsmentioning
confidence: 99%